2013
DOI: 10.1111/1477-8947.12009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geomorphology on the role of women at artisanal and small‐scale mine sites

Abstract: The geologic and geomorphic expressions of a mineral deposit determine its location, size, and accessibility, characteristics which in turn greatly influence the success of artisans mining the deposit. Despite this critical information, which can be garnered through studying the surficial physical expression of a deposit, the geologic and geomorphic sciences have been largely overlooked in artisanal mining‐related research. This study demonstrates that a correlation exists between the roles of female miners at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…These practices are different from those traditionally worked by men, as masculine mines are located at permanent extraction sites and require significantly higher degree of manual labor. This situation resembles the one described by Malpeli and Chirico (2013) for Western and Central Africa, in which the geomorphology of the mining sites was found to be a crucial characteristic with great influence in the gender roles of male and female in alluvial diamond and gold mining.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These practices are different from those traditionally worked by men, as masculine mines are located at permanent extraction sites and require significantly higher degree of manual labor. This situation resembles the one described by Malpeli and Chirico (2013) for Western and Central Africa, in which the geomorphology of the mining sites was found to be a crucial characteristic with great influence in the gender roles of male and female in alluvial diamond and gold mining.…”
Section: Resultssupporting
confidence: 80%
“…In fact, approximately 20% of global gold is extracted in this form (Armah, Boamah, Quansah, Obiri, & Luginaah, 2016). While artisanal gold mines can be diverse in their social and environmental nature, they are generally characterized by unmechanized operations, rudimentary tools, labor-intensive techniques, and small-scale extraction of ore (Lahiri-Dutt, 2015; Malpeli & Chirico, 2013).…”
mentioning
confidence: 99%
“…ASM industries are often perceived as male dominated despite women's ubiquitous involvement 4 ; "consequently, most research and policies have concentrated on men's jobs, while the contributions of women have been 'marginalized' and often overlooked" (Koomson, 2018: 101). Recent research has shed light on women's ASM participation (Buss et al, 2019;Hinton et al, 2017;Lahiri-Dutt, 2008;Lahiri-Dutt, 2015;Malpeli and Chirico, 2013). In Malian gold mining sites, women engage extra-marital relationships (petit mariage) that increase mineral access and represent a "pragmatic strategy to reduce risk and maximize benefit in a highly uncertain workplace" (Brottem and Ba, 2019: 56).…”
Section: Bodies and Geopolitics In Small-scale Gold Miningmentioning
confidence: 99%
“…They are not usually found digging the main ore bodies and going underground, but they may be found digging or panning around the edges, transporting, washing and processing. Malpeli and Chirico (2013) investigated 137 gold and diamond sites in West Africa over five years, collecting data directly from women at mine sites. They found that women's participation in mineral extraction was dependent on the thickness of the overburden and accessibility of the deposit, and that women were mostly involved in processing.…”
Section: Women In Asm: the African Perspectivementioning
confidence: 99%